1997
DOI: 10.1051/lait:1997436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk urea content on characteristics of matured Reblochon cheeses

Abstract: Summary -According to a crossed experimental design, two groups of 14 Montbéliarde dairy cows received in the winter two hay-based diets, with a normal or a high nitrogen level, obtained by substituting in the diet 2.5 kg of soybean meal to 2.5 kg of cereal concentrate. During the last week of the two experimental periods of 3 weeks, four batches of Reblochon cheese were manufactured with three different milks: control milk, milk from soya-fed cows and control milk with 0.25 gIL of added urea. Twenty-four batc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 12 publications
2
20
2
4
Order By: Relevance
“…4B). The addition of fluorofamide, a potent urease inhibitor, to the aspartate-supplemented milk confirmed that the reduction of the acidification rate detected near pH 6 was related to urea hydrolysis as previously demonstrated (22,26,28). Moreover, the addition of fluorofamide in aspartate-supplemented milk allowed mutant A18(⌬ppc) to reach a pH value similar to that of the parental strain.…”
Section: Streptococcus Thermophilus Dsm 20617supporting
confidence: 84%
“…4B). The addition of fluorofamide, a potent urease inhibitor, to the aspartate-supplemented milk confirmed that the reduction of the acidification rate detected near pH 6 was related to urea hydrolysis as previously demonstrated (22,26,28). Moreover, the addition of fluorofamide in aspartate-supplemented milk allowed mutant A18(⌬ppc) to reach a pH value similar to that of the parental strain.…”
Section: Streptococcus Thermophilus Dsm 20617supporting
confidence: 84%
“…Under extensive farming system (farm A), the higher cheese yield was linked to the higher casein content that characterized the low milk produced by the rustic autochthonous Sicilian cows, whereas the lower cheese fat was probably connected to the milking system of the autochthonous cows, according to which the last and most fat rich-milk is destined for the calf (Alabiso et al, 2000). Moreover, in cheeses from farm A, the lower NaCl may depend on the higher moisture which diluted the salt, the lower N soluble content may reflect the lower milk urea (Martin et al, 1997), and the lower yellow index (b*) was probably due to a lower level of carotenoids in comparison with the cheese from intensive farm B where the cows consumed a maize-based concentrate. The strong pressure action exerted on the cheese paste to eliminate the residual whey during the traditional cheese making technology (Tornamb e et al, 2009) may be responsible for the higher DM, the reduced cheese yield, and the more compact cheese paste in comparison with the standard technology.…”
Section: Discussionmentioning
confidence: 99%
“…It is not just a seasonal effect stricto sensu: the differences observed are probably linked to the seasonal changes in the chemical and microbiological characteristics of milk, to the cheese plant environmental conditions and to certain technological parameters that may have evolved from one cheesemaking season to the other. Thus, the less firm texture of summer cheeses could be linked both to their lower dry matter content and higher fat content (linked to the fat to protein ratio being standardised at 1.13 vs. 1.05-1.08 during other periods) as well as to higher urea concentration in milk [13]. It is certainly also partially explained by the type of forage fed to cattle (pastured or preserved grass) [20] and by the changes in the cows' physiological condition [7].…”
Section: Discussion-conclusionmentioning
confidence: 99%